2019
DOI: 10.3390/su11195251
|View full text |Cite
|
Sign up to set email alerts
|

Travel Behavior of Elderly in George Town and Malacca, Malaysia

Abstract: We investigated the travel behavior of the elderly in two United Nations Educational, Scientific and Cultural Organization UNESCO Heritage Cities in Malaysia, George Town and Malacca, to assess the commonalities and differences in the mobility of the elderly and to analyze the factors influencing the mobility of the elderly. We relied upon a one-day travel diary where the elderly recorded their trip information including trip category, mode of travel, and distance travelled. A total of 455 travel diaries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 55 publications
(60 reference statements)
0
33
0
Order By: Relevance
“…It is not surprising that a majority of tourists, especially seniors, are concerned about the safety and cleanliness of tourism attractions as these are basic factors for traveling (Abooali et al, 2015;Esichaikul, 2012;Jang & Wu, 2006). Moreover, seniors are more concerned about medical and health treatment, which is consistent with the inevitable decline of health and the physical barriers that are universal consequences of aging (Mohamed et al, 2016). Notably, both senior and future senior tourists valued "seniors-only accommodation options" as the least important attribute (seniors = 3.68, future seniors = 3.58).…”
Section: Descriptive Statistics and Paired Sample T Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising that a majority of tourists, especially seniors, are concerned about the safety and cleanliness of tourism attractions as these are basic factors for traveling (Abooali et al, 2015;Esichaikul, 2012;Jang & Wu, 2006). Moreover, seniors are more concerned about medical and health treatment, which is consistent with the inevitable decline of health and the physical barriers that are universal consequences of aging (Mohamed et al, 2016). Notably, both senior and future senior tourists valued "seniors-only accommodation options" as the least important attribute (seniors = 3.68, future seniors = 3.58).…”
Section: Descriptive Statistics and Paired Sample T Test Resultsmentioning
confidence: 99%
“…Future seniors are individuals who are about to enter the senior age phase in a few years (Mohamed et al, 2016). Research has revealed that future senior generations will behave more like the current population of the same age and show no decline in travel propensity as they move from their late middle to early senior years (You et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…One study in Wenling, China shows that elderly who do not work and have more free time are more likely to walk (Ren et al 2018). In studies conducted in Latin America and Malaysia, elderly cohorts were found to walk more than younger ones (Mohd et al 2019;Ferrari et al 2020). Moreover, Adeel et al (2017) found that Pakistani elderly men take frequent walking trips to nearby social and religious places.…”
Section: Trip Mode Choicementioning
confidence: 99%
“…The literature shows great variation in older adults' usage of PT in the Global South. For example, less than 4% of elderly in Malacca, Malaysia use PT (Mohd et al 2019), whereas in Hong Kong, nearly 90% of the total population uses PT and bus travel represents the highest percentage of daily travel for older adults (Szeto et al 2017). Additionally, the use of PT differs depending on socio-economic status, age, and gender.…”
Section: Public Transport (Pt)mentioning
confidence: 99%
“…For example, Habib and Hui (2017) indicated that spatial accessibility to various activity locations is a crucial factor in defining the daily out-of-home activity participation of older people. Mohd et al (2019) found that location (city), education level, private vehicle ownership, health status and exercise participation are factors significantly affecting elderly travel frequency. Böcker et al (2017) comprehensively analysed the influence of socio-demographic, health, trip, spatial and weather attributes on elderly mobility with zero-inflated negative binomial and multinomial logit regression models.…”
Section: Introductionmentioning
confidence: 99%